Extract of olive fruit fly males (Diptera: Tephritidae) attract virgin females - Mavraganis, V.G.; Papadopoulos, N.T.; Kouloussis, N.A. (ENTOMOLOGIA HELLENICA, 2017)
Research conducted during the past three decades suggests that in contrast to most other tephritid fruit flies, in which sexual pheromones are produced by males, the olive fruit fly Bactrocera oleae (Rossi) relies for its sexual communication on a pheromone that is produced by females. However, our present study suggests that virgin, mature females are attracted to male odors. In olfactometer assays extracts of male bodies obtained with a two-solvent system of methanol and dichloromethane were highly attractive to virgin females. This was observed during the last two hours of the photophase, when males are sexually active, but not during the first hours of the photophase, or when mated females were tested. Extracts of male bodies obtained with diethyl ether were also attractive to virgin females, albeit not as strongly as the two-solvent extracts. These results strongly indicate that males of the olive fruit fly elicit attraction to virgin females based on olfactory stimuli. The importance of these findings for understanding the sexual behavior of the olive fruit fly is discussed.